2019
DOI: 10.1093/pm/pnz219
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Chiropractic Use and Opioid Receipt Among Patients with Spinal Pain: A Systematic Review and Meta-analysis

Abstract: Objective To investigate the current evidence to determine if there is an association between chiropractic use and opioid receipt. Design Systematic review and meta-analysis. Methods The protocol for this review was registered on PROSPERO (CRD42018095128). The MEDLINE, PubMed, EMBASE, AMED, CINAHL, and Web of Science databases were searched for relevant artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 28 publications
8
38
0
Order By: Relevance
“…For example, although our data were insufficient to analyze for risk of opioid use, several recent studies have found that utilization of nonpharmacologic pain therapies leads to decreased opioid use. [17][18][19][20][21] Future research could explore the benefit of the PSC model in reducing overprescription of opioids. Additionally, we cannot be certain that variation in access to care was identical across the 3 sites; however, the 3 sites are part of the same health care system that strives for standardization, including monitoring a metric from time of patient call to time seen in clinic.…”
Section: T a G G E D H 1 Discussiont A G G E D E N Dmentioning
confidence: 99%
“…For example, although our data were insufficient to analyze for risk of opioid use, several recent studies have found that utilization of nonpharmacologic pain therapies leads to decreased opioid use. [17][18][19][20][21] Future research could explore the benefit of the PSC model in reducing overprescription of opioids. Additionally, we cannot be certain that variation in access to care was identical across the 3 sites; however, the 3 sites are part of the same health care system that strives for standardization, including monitoring a metric from time of patient call to time seen in clinic.…”
Section: T a G G E D H 1 Discussiont A G G E D E N Dmentioning
confidence: 99%
“…A few case reports similarly described patient medication reduction or elimination through the utilization of MMT [47,48,56,67], but most did not comment on any change in medication. A recent systematic review and meta-analysis revealed an inverse association between chiropractic care and opioid receipt in veterans with spinal pain [79] and multiple cohort studies of health insurance claims data displayed a significantly lower likelihood of filling opioid prescriptions for recipients of chiropractic care than nonrecipients [80,81]. Although promising, it is not clear if this relationship persists in the post-surgical population.…”
Section: Medicationsmentioning
confidence: 99%
“…1,2 Back, neck, and shoulder pain are leading causes of disability in Canada 3 and are among the most common reasons for prescribing opioids. 4,5 Clinical practice guidelines emphasize non-pharmacological management of pain as the first line approach for chronic non-cancer pain including MSK conditions. 6,7 However, cost presents a significant barrier for those without public or private insurance.…”
Section: Overcoming Pain As a Barrier To Employment: Health2work Program Integrates Chiropractic Care And Social Services In Waterloo Regmentioning
confidence: 99%